Pop Up Book sebagai Media Pembelajaran dalam Upaya Meningkatkan Minat Belajar dan Membaca Siswa di SDN Panempan 1 Pamekasan - Windayati, Windayati; Rozi, Mohammad Fahrur; Abdurahman, Abdurahman (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Using learning media in the form of Pop up Book, students are expected to be able to more easily understand the subject matter in class and increase their interest in reading, thus having a positive impact on students' overall reading progress. Methodology: Teaching activities in the classroom, helping to improve the quality of education in schools, helping to adapt the use of Pop up Book media in schools, and helping to ease the teacher's task for students who need special handling related to reading. Results: As many as 85% of students are able to use Pop up Book learning media well, while some teachers still do not know what Pop up Book learning about media. Conclusions: The use of Pop-up Book as a learning media during lessons helps students easily understand the subject matter and achieve satisfying learning outcomes. Additionally, when students turn each page of the book, standing images appear, creating an impression of pictures and illustrations that foster an enjoyable and non-monotonous learning atmosphere. Satisfying learning outcomes will help achieve learning objectives optimally. Moreover, the use of learning media provides a comfortable learning environment, as students are no longer solely focused on the teacher delivering the material. Limitations: The limitation of this programme is the timing. Contribution: The use of Pop up Book media can help expand the knowledge of students and teachers.